Understanding First-Time Voters' Desires in Ward No. 30 of Rajshahi City Corporation: A Quantitative Inquiry - Alam , Md. Mahbubul; Arafat, Md. Yeasir; Fahmida; Namisa Tabassum (Penerbit Hellow Pustaka, 2026)
This research initiates an inquiry into the perceptions, expectations, and political behavior of first-time voters of Ward No. 30, Rajshahi City Corporation to gauge their role in the democratic process as new entrants in the electoral system. First-time voters provide an insightful view of how youth relate to democracy in Bangladesh. The study uses a structured questionnaire with demographic and issue-based questions to show key concerns at present: unemployment, corruption, and low faith in electoral fairness. It further probes what influences their voting decision—credibility of the candidate, party ideology, or social media and peer influence—and finds that first-time voters have a very sophisticated awareness of politics; they are both enthusiastic and skeptical about such voters who demand accountability with transparent and inclusive governance. The findings show a sophisticated political sensitivity among first-time voters—a mix of zeal and doubt—who weigh much accountability, transparency, and inclusive governance. It is thus concluded that by giving this demographic more political representation and real engagement opportunities, a more participatory and responsive democratic culture can be encouraged.